Accounts Payable (Qardh) in Islamic Law - Saprida Saprida; Choiriyah Choiriyah; Melis Melis (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThis study discusses how accounts receivable (qardh) are in Islamic law. This research is a type of library research that focuses on qualitative data management with data analysis methods using the description-analysis method. The results of this study are that qardh (accounts receivable) is an act or activity that has the purpose of helping others who are in need of material assistance, and is highly recommended because it provides wisdom and benefits for the lender and the recipient of the debt. Qardh is permissible as long as there are no elements which are detrimental to either party. While the law exceeds the payment of as much debt, if the excess is indeed the will of the debtor and not the previous agreement, then the excess may be for those who repay it, and be good for those who pay the debt. As for the additions that are desired by those who are in debt or have become agreements during the contract, this must not be prohibited in Islam.Keywords: Qardh, Islamic Law. AbstrakPenelitian ini membahas bagaimana piutang (qardh) dalam hukum Islam. Penelitian ini adalah jenis penelitian kepustakaan yang berfokus pada manajemen data kualitatif dengan metode analisis data menggunakan metode deskripsi-analisis. Hasil penelitian ini adalah bahwa qardh (piutang dagang) adalah tindakan atau kegiatan yang memiliki tujuan membantu orang lain yang membutuhkan bantuan material, dan sangat dianjurkan karena memberikan kebijaksanaan dan manfaat bagi pemberi pinjaman dan penerima hutang. Qardh diperbolehkan selama tidak ada unsur yang merugikan salah satu pihak. Sementara hukum melebihi pembayaran hutang sebanyak-banyaknya, jika kelebihannya memang merupakan kehendak debitur dan bukan perjanjian sebelumnya, maka kelebihannya mungkin bagi mereka yang membayarnya, dan baik bagi mereka yang membayar hutang. Adapun tambahan yang diinginkan oleh mereka yang berhutang atau telah menjadi perjanjian selama kontrak, ini tidak boleh dilarang dalam Islam.Kata kunci: Qardh, Hukum Islam.